Concentration of Natural Radionuclide and Potential Radiological Dose of 226Ra to Marine Organism in Tanjung Awar-Awar, Tuban Coal-Fired Power Plant - Chairun Annisa Aryanti; Heny Suseno; Muslim Muslim; Wahyu Retno Prihatiningsih; Mohamad Nur Yahya (Jurnal Segara, 2021)
Fly ash and bottom ash from coal combustion can contain natural radionuclides with a certain concentration. The release of fly ash into the environment can potentially increase the concentration of natural radionuclides in the surrounding environment, including marine waters. This study aimed to determine the activity of natural radionuclides in seabed sediments and the radiological impact on marine organisms related to Tanjung Awar-Awar Coal-Fired Power Plant activities in Tuban. The sampling techniques were carried out by the purposive sampling method. The concentration measurement of natural radionuclide activity was carried out using HPGe detector gamma-ray spectrometry at marine radioecology laboratory of National Nuclear Energy Agency. The detected concentration of natural radionuclide activity was 40K ranging from 159.18 to 365.88 Bq.Kg-1, 228Ac ranging from 14.47 to 28.05 Bq.Kg-1, and 226Ra ranging from 15.00 to 67.65 Bq.Kg-1. By using the ERICA Assessment Tool Tier 2 program, the results of the analysis showed that there was no impact of 226Ra radiation on marine organisms at the research site because the total radiation dose rate (external + internal) of 226Ra on marine biota was lower than the screening level of 10 μGy / h. Thus, it will not harm marine ecosystems and the sustainability of marine organisms in the waters of Tanjung Awar-Awar Coal-Fired Power Plant, Tuban.